2020
DOI: 10.3390/ijerph17082886
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Health Literacy in Facilities for People with Disabilities: First Results of an Explorative Qualitative and Quantitative Study

Abstract: To date, studies on individual and organizational health literacy (OHL) in facilities for people with disabilities are scarce. Thus, the aims of this study are (1) to adapt an existing instrument for measuring organizational health literacy (OHL), namely, the “Health literate health care organization scale” (HLHO-10), to the context of facilities for people with disabilities, (2) to quantitatively examine characteristics of OHL, and (3) to qualitatively assess the definition and role of OHL by interviewing man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 48 publications
0
8
0
4
Order By: Relevance
“…In "Potentials of School Nursing for Strengthening the Health Literacy of Children, Parents and Teachers", Buhr et al [73] conducted a pilot study in Germany, finding promisingly that school nurses may contribute to strengthening health literacy within the school setting. Rathmann and colleagues [74] consider the organizational health literacy in facilities for people with disabilities in their pilot mixed-methods study: "Organisational Health Literacy in Facilities for People with Disabilities: First Results of an Explorative Qualitative and Quantitative Study". Domanska et al [75] provide new evidence around self-reported health literacy in adolescence in "Development and Psychometric Properties of a Questionnaire Assessing Self-Reported Generic Health Literacy in Adolescence".…”
Section: Organizational Level: Schools Students and Adolescentsmentioning
confidence: 99%
“…In "Potentials of School Nursing for Strengthening the Health Literacy of Children, Parents and Teachers", Buhr et al [73] conducted a pilot study in Germany, finding promisingly that school nurses may contribute to strengthening health literacy within the school setting. Rathmann and colleagues [74] consider the organizational health literacy in facilities for people with disabilities in their pilot mixed-methods study: "Organisational Health Literacy in Facilities for People with Disabilities: First Results of an Explorative Qualitative and Quantitative Study". Domanska et al [75] provide new evidence around self-reported health literacy in adolescence in "Development and Psychometric Properties of a Questionnaire Assessing Self-Reported Generic Health Literacy in Adolescence".…”
Section: Organizational Level: Schools Students and Adolescentsmentioning
confidence: 99%
“…HLHO-10 scale was also adapted to measure and use the OHL level of the facilities established for individuals with various disabilities [35].…”
Section: Communicates Clearly What Health Plans Covermentioning
confidence: 99%
“…Gemeinsam ist allen Definitionen das Verständnis, dass unter der organisationalen Gesund-heitskompetenz alle Bemühungen einer Einrichtung verstanden werden, die allen Akteuren und Nutzergruppen -wie Mitarbeitenden (d. h. Leitungs-, Fach-und Betreuungspersonal) und insbesondere Menschen mit eingeschränkten kognitiven oder sprachlichen Fähigkeitenden Umgang mit gesundheitsbezogenen Informationen und der Gesundheit allgemein erleichtern. Auch sind einrichtungsspezifische Materialien, Leistungen und die Kommunikation derart zu gestalten, dass sie der individuellen Gesundheitskompetenz der Nutzenden zuträglich sind und auf die eigenen gesundheitlichen Belange angewendet werden können [17,21,23,26]. Die organisationale Gesundheitskompetenz kann, je nach Konzept, in acht bis zehn Handlungsfelder bzw.…”
Section: Tools Zur Stärkung Der Organisationalen Gesundheitskompetenz In Einrichtungen Für Menschen Mit Behinderung: Eine Systematische üunclassified
“…Im Vergleich zu Krankenhäusern ist in Einrichtungen der Behindertenhilfe von einer geringeren Fluktuation der Klient*innen auszugehen. Eine Studie zur organisationalen Gesundheitskompetenz in Einrichtungen der Behindertenhilfe konnte darlegen, dass die Orientierung zur und innerhalb der Einrichtung aus Sicht der Einrichtungsleitungen und der Mitarbeitenden als nicht relevant für außenstehende Nutzende betrachtet wurde [23]. Vor dem Hintergrund des Inklusionsgedankens und der barrierefreien Gestaltung von Einrichtungen ist dies künftig kritisch zu hinterfragen.…”
Section: Entwicklung Von Dokumentenunclassified